A high-speed electrospinning method based on inorganic molecular chain solution

By synergistically designing a high-solids-content inorganic molecular chain solution, a high-speed uniform-pressure spinneret, and a wall-mounted guide-directional pressurization nozzle, the problems of slow spinning rate and uneven liquid supply in the preparation of ceramic nanofibers were solved, thus achieving high-speed preparation and refinement of ceramic nanofibers.

CN122327414APending Publication Date: 2026-07-03DONGHUA UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610372382.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-03-25
Publication Date
2026-07-03

Smart Images

  • Figure CN122327414A_ABST
    Figure CN122327414A_ABST
Patent Text Reader

Abstract

This invention relates to a high-speed electrospinning method based on an inorganic molecular chain solution. The method involves sequentially adding a linear-rigid bidentate linker, a bidentate stabilizer, acid, water, a chain extender, and a UV-responsive end-capping agent to a metal alkoxide monomer solution. Following hydrolysis, polycondensation, chain extension, and end-capping reactions, a high-polymerization-degree linear inorganic molecular chain is synthesized. This chain is then mixed with a low-polymerization-degree linear molecular chain solution, and a cationic component is introduced to obtain a high-solids-content spinning solution with a bimodal molecular weight distribution. This spinning solution is then uniformly distributed by a high-speed, pressure-equalizing spinneret and delivered to an attached-wall guiding-directional pressurized nozzle. Under the synergistic effect of an electrostatic field and a high-speed thin-layer airflow guided by an annular guide protrusion within the nozzle and tangential to the surface of a Taylor cone, precursor nanofibers are obtained. High-temperature calcination yields ceramic nanofiber materials. Compared to existing technologies, this invention significantly improves the spinning rate per nozzle and produces ultrafine fibers with uniform diameter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrospinning preparation technology of inorganic fibers, and in particular to a high-speed electrospinning method based on inorganic molecular chain solutions. Background Technology

[0002] Ceramic nanofibers possess advantages such as high specific surface area, good chemical stability, and high temperature resistance, demonstrating enormous application potential in fields such as adsorption separation, high-temperature insulation, sound absorption and noise reduction, and biomedicine. Currently, electrospinning has become the mainstream method for preparing ceramic nanofibers due to its wide range of applicable raw materials and fine fiber diameter. However, this method relies solely on relatively weak electrostatic force as the single stretching force, resulting in a slow fiber preparation rate; furthermore, the low solid content of existing inorganic spinning solutions further limits the spinning rate.

[0003] To address the aforementioned problems, existing technologies typically employ coaxial nozzles to introduce auxiliary airflow to improve fiber-forming efficiency. Patent application ZL201520873723.2 discloses an airflow-assisted electrospinning annular nozzle and electrospinning device. This device surrounds the nozzle with a closed annular airflow cavity and introduces room-temperature or heated nitrogen gas from the lower end of the cavity to stretch the spinning jet, thereby improving spinning efficiency to some extent. However, this device lacks an airflow guiding structure at the nozzle, preventing the ejected airflow from forming a tangential interaction with the Taylor cone. The jet is stretched solely by the clamping effect of the airflow, making it difficult to achieve high-speed jet ejection. Patent application ZL202120636449.2 discloses an airflow-assisted coaxial nozzle. By providing a coaxial gas channel outside the spinning liquid channel and employing an inclined nozzle shell design, the airflow can form a tangential interaction with the Taylor cone, increasing the jet ejection speed. However, due to the large nozzle diameter and high jet flow rate, the airflow is difficult to dissipate quickly after ejection, thus affecting the whipping refinement of the jet in the whipping region. The aforementioned nozzle primarily improves the spinning rate by altering its structure, neglecting the influence of the spinning solution and supply device on the spinning rate, thereby limiting further high-speed preparation of ceramic nanofibers.

[0004] Existing technological improvements have focused on localized optimization of the nozzle structure, failing to fundamentally address the two other core bottlenecks hindering the high-speed production of ceramic nanofibers: first, the inorganic precursor solutions suitable for electrospinning have low solid content and poor spinnability, resulting in insufficient total amount of fiber-forming material that can be sprayed per unit time; second, high-viscosity, high-solid-content spinning solutions are difficult to distribute and transport uniformly, stably, and at high pressure under multi-nozzle conditions. Therefore, to achieve high-speed industrial production of ceramic nanofibers, it is essential to abandon the approach of simply improving the nozzle structure and instead seek a holistic solution that achieves synergistic breakthroughs in both solution property control and equipment system innovation, simultaneously tackling the three major technical challenges of high-solid-content spinning solution preparation, high-speed and stable solution supply, and efficient drawing and refining. Summary of the Invention

[0005] The purpose of this invention is to overcome the defects of the prior art by providing a high-speed electrospinning method based on inorganic molecular chain solutions. By using molecular design to obtain an inorganic spinning solution with high solid content and excellent spinnability, and combining it with a dedicated nozzle that can efficiently tangentially traction jet and has little interference in the whipping region, as well as a pressure equalization liquid supply system, the invention achieves high-speed preparation of ceramic nanofibers while ensuring diameter by working together in terms of solution, liquid supply, and drawing.

[0006] The objective of this invention can be achieved through the following technical solutions: This invention provides a high-speed electrospinning method based on an inorganic molecular chain solution, comprising the following steps: S1. A linear-rigid bidentate linker is added to a metal alkoxide monomer solution to linearly link the monomers. Then, a bidentate stabilizer is added to form a linear pre-coordinated framework. Subsequently, acid and water are added to perform hydrolysis and polycondensation to obtain low-polymerization-degree linear inorganic molecular chains. Then, a chain extender is added to extend the chain. A UV-responsive end-capping agent is added, and UV light irradiation is used to end the linear inorganic long chains with the end-capping agent, thereby controlling the degree of polymerization of the molecular chains and obtaining linear inorganic molecular chains with different degrees of polymerization. S2. Prepare spinning solutions for the high-polymerization degree and low-polymerization degree molecular chains obtained in S1 respectively, and mix the two solutions to obtain a high-solids content spinning solution with a bimodal molecular weight distribution. Introduce cationic components into the mixed solution to regulate its solution properties. S3. The spinning solution prepared in step S2 is transported to a high-speed pressure equalizing spinneret. After pressure equalization through the multi-stage liquid distribution holes and liquid supply buffer chamber inside the high-speed pressure equalizing spinneret, it is introduced into the wall-mounted guide-directional pressurization nozzle. At the same time, airflow is introduced into the air inlet of the wall-mounted guide-directional pressurization nozzle. Under the combined action of the electrostatic field and the high-speed airflow tangential to the surface of the Taylor cone after being guided by the annular guide protrusion inside the nozzle, the spinning solution jet achieves high-speed jetting in the stable region. In the whipping region, it is fully stretched and refined under the enhanced charging effect of the cationic component, thereby obtaining precursor nanofibers. S4. High-temperature calcination: The precursor nanofibers obtained in S3 are subjected to high-temperature calcination to obtain ceramic nanofiber materials.

[0007] Further, in S1, the metal alkoxide is selected from indium isopropoxide, indium triethoxy, indium tert-butoxide, titanium tetraethanol, titanium isobutoxide, titanium n-propoxide, titanium n-butoxide, titanium tetramethanol, titanium tert-butoxide, titanium isooctanol, titanium tetrapentoxide, titanium isopropoxide, zirconium tetraethanol, zirconium tetrapropoxide, zirconium isopropoxide, zirconium n-propoxide, zirconium isobutoxide, zirconium tert-butoxide, zirconium n-butoxide, zirconium tetrapentoxide, aluminum n-butoxide, aluminum trimethoxy, aluminum tri-n-propoxy, aluminum isopropoxide, and sec-butoxide. Aluminum alkoxide, aluminum triethanolamine, aluminum tert-butoxide, tin n-propoxide, tin n-butoxide, tin tetramethanol, tin tert-butoxide, tin tetraethanolamine, tin isobutoxide, tin isopropoxide, tin tetrapentanol, gallium isopropoxide, gallium triethoxy, gallium n-butoxide, gallium tert-butoxide, hafnium tetramethanol, hafnium tetraethanolamine, hafnium n-propoxide, hafnium isopropoxide, hafnium n-butoxide, hafnium tert-butoxide, hafnium tetrapentanol, tantalum isopropoxide, tantalum n-butoxide, niobium isopropoxide, niobium n-butoxide; one or more combinations thereof; The bidental connector is selected from one or more of p-phenylenediamine, 1,4-naphthylenediamine, 1,4-benzenediol, and terephthalic acid; The didentate stabilizer is selected from one or more of ethylenediamine, acetylacetone, and tetramethylethylenediamine; The chain extender is selected from one or more of the following: diisopropoxydiacetylacetonate titanium, bis(ethyl acetoacetate)titanate diisopropyl ester, bis(diethylcitrate)dipropoxide zirconium, (ethyl acetoacetate)diisopropoxyaluminate, titanium dichlorodecene, zirconium dichlorodecene, hafnium dichlorodecene, molybdenum dichlorodecene, vanadium dichlorodecene, and niobium dichlorodecene. The UV-responsive end-capping agent is selected from one or more of 4-azidobenzoic acid, 3-azidopropyltrimethoxysilane, and 1,3-dioxopentanepropyltrimethoxysilane.

[0008] Further, in S1, the degree of polymerization of the low-polymerization-degree linear inorganic long chain is 200~1000, and the degree of polymerization of the high-polymerization-degree linear inorganic long chain is 2000~5000. In S2, the inorganic molecular chain solution has a solid content of 30~70wt%, a viscosity of 10~10000mPa·s, an electrical conductivity of 0.1~1000μS / cm, a surface tension of 30~120mN / m, and a specific viscosity of 0.3~0.9.

[0009] Further, in S2, the cationic component is introduced in the form of a compound selected from one or more of hydrochloric acid, phosphoric acid, formic acid, acetic acid, propionic acid, butyric acid, lactic acid, oxalic acid, malonic acid, succinic acid, citric acid, sodium chloride, lithium chloride, potassium chloride, magnesium chloride, calcium chloride, barium chloride, zinc chloride, ferric chloride, sodium carbonate, potassium carbonate, silver nitrate, copper nitrate, lithium bromide, tetrabutylammonium bromide, tetrabutylammonium chloride, and tetraethylammonium chloride. The compound is used to improve the jet charging characteristics and reduce the electrostatic adsorption between inorganic molecular chains, thereby enhancing the whipping and refining ability of the jet in the electrostatic field.

[0010] Furthermore, in S3, the main body of the high-speed pressure equalizing liquid supply spinneret is provided with an inlet and an outlet, and the interior of the high-speed pressure equalizing liquid supply spinneret is provided with a liquid distribution hole, a baffle plate, a liquid supply buffer chamber, and a conveying channel. The baffles are distributed at intervals from bottom to top inside the high-speed pressure equalizing liquid supply spinneret, and a liquid supply buffer cavity is formed between two adjacent baffles. The liquid separation orifice is located on the barrier plate; The liquid distribution holes on each layer of the barrier plate are arranged at intervals along the spinneret axis, and the number of liquid distribution holes increases progressively from bottom to top in the direction of the barrier plate. The liquid inlet is located on both sides of the main body of the high-speed pressure equalizing liquid supply spinneret, and the liquid inlet is connected to the liquid supply buffer chamber at the bottom layer. The beginning of the conveying channel is connected to the liquid distribution hole on the top layer barrier plate, and the end of the conveying channel is connected to the liquid outlet. The liquid outlet is located at the bottom of the high-speed pressure equalizing liquid supply spinneret; After the spinning solution is introduced into the spinneret through the inlet, it is conveyed upward through the distribution holes on the baffle plate and collected at the upper end of the high-speed pressure equalizing spinneret into the conveying channel. Then it is supplied to each wall-mounted guide-directional pressurizing nozzle installed below it through the outlet. The above structural design enables the spinneret to uniformly distribute the spinning solution under high-speed liquid supply conditions, and achieves stable and high-speed liquid supply to each nozzle.

[0011] Furthermore, the diameter of the liquid distribution holes is 0.1~2.0mm, and the total number is 2~200. The shape of the liquid distribution holes is selected from one of the following: circular, elliptical, rhomboid, and slit, to adapt to spinning solutions with different rheological properties. The high-speed pressure equalizing spinneret is made of a corrosion-resistant material, which is selected from one or more of stainless steel, titanium alloy, aluminum alloy, nickel-based alloy, and high-strength engineering resin.

[0012] Furthermore, in S3, each wall-mounted guide-directional pressurization nozzle adopts a split modular structure, and each wall-mounted guide-directional pressurization nozzle includes a fluid feed assembly and an exhaust housing; The fluid feeding assembly includes a fluid feeding assembly outer tube body, a solution channel tube disposed inside the fluid feeding assembly outer tube body and arranged axially, and a liquid outlet needle connected to the end of the solution channel tube. The air outlet shell is threadedly connected to the end of the fluid feeding assembly outer tube body. An annular airflow channel is formed between the outer wall of the solution channel tube and the liquid outlet needle and the inner wall of the fluid feeding assembly outer tube body and the inner wall of the air outlet shell. The upper end of the outer tube body of the fluid feed assembly is provided with an external thread interface, and the bottom surface of the body of the high-speed equalizing liquid supply spinneret is provided with multiple internal thread interfaces that match the external thread interface at the corresponding liquid outlet position. The outer tube body of the fluid feed assembly is threadedly connected to the bottom surface of the body of the high-speed equalizing liquid supply spinneret. The airflow channel is provided with a gas regulating component, which includes a baffle plate and a plurality of regulating holes thereon; The plurality of regulating holes are arranged in a ring around the outside of the solution channel tube, and their diameters are set in a gradient decreasing along the transverse direction of the baffle plate, for the purpose of equalizing and distributing the incoming airflow.

[0013] Furthermore, the bottom end of the air outlet shell is provided with a wall-mounted flow guiding-directional pressurization structure, which includes an annular flow guiding protrusion and a conical converging outer wall. The annular flow guiding protrusion surrounds the outside of the liquid outlet needle, and a radially narrowing air outlet gap is formed between the annular flow guiding protrusion and the conical converging outer wall. The width of the radial air outlet slit gradually decreases along the airflow direction to accelerate the airflow and form a high-speed thin-layer airflow. The annular guide protrusion guides the flow direction of the high-speed thin-layer airflow, ensuring that it is tangential to the surface of the Taylor cone of the spinning solution ejected from the liquid outlet needle when it is ejected, thereby creating directional traction on the jet. The high-speed thin-layer airflow dissipates rapidly in the whipping zone to avoid interfering with the jet stretching and refining process. Because the airflow velocity varies in different areas when entering the nozzle, the orifice diameter is smaller near the airflow (high velocity) and larger away from the air inlet (low airflow velocity) (see...). Figure 8 This corrects the initial airflow velocity; the aperture gradient decreases from the nine o'clock position to the three o'clock position, making the airflow in different areas more uniform as it flows downwards.

[0014] Furthermore, an elastic seal is provided at the connection between the fluid feed assembly and the air outlet housing, which ensures the sealing performance of the solution channel pipe 24 and the airflow channel, as well as the stability of the overall nozzle structure, while enabling quick assembly and disassembly. The thickness of the gas regulating component is 0.1~0.4mm, and the diameter of the regulating hole is 0.3~0.9mm; In the wall-mounted guide-directional pressurization structure, the axial length of the annular guide protrusion is 1.5 to 3.0 times the width of the radial air outlet gap, and the radial thickness of the annular guide protrusion is 0.2 to 1 times the outer diameter of the liquid outlet needle. The conical converging outer wall is configured as a converging structure along the axial direction of the nozzle, with a converging half angle of 3~20° relative to the nozzle axis, and the minimum radius of curvature of the conical converging outer wall is 0.3~1.2 times the outer diameter of the liquid outlet needle. The radial width of the radial air outlet gap is 0.1~1mm.

[0015] Furthermore, the high-speed pressure equalizing liquid supply spinneret is connected to a high-voltage power supply. By adjusting the output voltage to -120~120kV, the airflow velocity to 0~100m / s, the injection speed of the spinning solution to 10~200mL / h, the receiving distance between the liquid outlet needle and the spinning receiving device to 30~50cm, the spinning environment temperature to 25~35℃, and the environmental humidity to 20~90%, the spinning jet can achieve high-speed fiber formation and refinement. The prepared fibers have a diameter of 50~500nm and a single-nozzle spinning rate of 2~10kg / day.

[0016] The mechanism of this invention is described below: (1) The present invention adopts a high-speed pressure equalizing spinneret. After the spinning liquid enters the spinneret, it is sequentially divided by small-diameter distribution holes set on the baffle plate. The distribution holes generate equalization and pressure division effects on the spinning liquid under high-speed liquid supply conditions, thereby effectively reducing the pressure difference of the spinning liquid in the axial direction and making the spinning liquid obtain a more balanced distribution state in the axial direction. The spinning liquid after primary diversion then enters the liquid supply buffer chamber, and under the continuous equalization and pressure division effects of each level of distribution holes, a fluid state with uniform pressure and mass distribution is formed, which is conducive to achieving subsequent rapid and stable liquid supply.

[0017] (2) The present invention provides a tapered wall-mounted guide-directed pressurization structure at the bottom of the nozzle outlet shell, so that the airflow generates the Coanda effect at this structure. Under the action of this effect, the airflow flows along the annular guide protrusion and gradually thins, and the outlet gap is tapered, which further reduces the flow cross section of the airflow, and finally forms a high-speed thin-layer airflow; and as the shape of the curved outer wall changes, its flow direction gradually deflects, and finally it is ejected at the nozzle in a manner tangential to the surface of the Taylor cone, thereby driving the jet to be ejected at high speed in the stable region and rapidly dissipated in the whipping region.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention achieves efficient spinning of inorganic long chain jet by preparing a high solid content inorganic molecular chain spinning solution system and combining the synergistic design of a high-speed equal pressure supply spinneret and a wall-mounted guide flow directional pressurization nozzle, thereby significantly improving the spinning rate of a single nozzle, which can reach up to 2~10 kg / day.

[0019] (2) The present invention introduces cationic components into the inorganic molecular chain spinning solution to increase the overall charge of the jet and reduce the electrostatic adsorption between inorganic molecular chains, thereby enhancing the Rayleigh instability of the jet in the whipping region, so that the jet can be more fully whipped and refined, and finally obtain nanofibers with a diameter of 50~500nm. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the spinneret and nozzle assembly. Figure 2 A schematic diagram of a side cross-section of a high-speed pressure equalizing spinneret; Figure 3 Schematic diagram of the liquid outlet of a high-speed pressure equalizing spinneret; Figure 4 A schematic diagram of the internal flow channel of a high-speed pressure equalizing spinneret; Figure 5 A schematic cross-sectional view of the liquid outlet transition point of a high-speed pressure equalizing liquid supply spinneret. Figure 6 A schematic diagram of the internal structure of a wall-mounted flow guide-directional pressurization nozzle; Figure 7 This is a schematic diagram of the cross-section of the fluid feed assembly; Figure 8 This is a schematic diagram of the gas regulation component structure; Figure 9 This is a schematic diagram of a wall-mounted flow guide-directional pressurization structure.

[0021] The diagram is labeled as follows: 1-High-speed equalizing liquid supply spinneret, 2-Wall-attached guide-directional pressurization nozzle, 3-Liquid inlet, 4-Distribution hole, 5-Baffle plate, 6-Liquid supply buffer chamber, 7-Transport channel, 8-Liquid outlet, 9-Cross-section view of the internal flow channel of the high-speed equalizing liquid supply spinneret, 10-Flow direction of spinning solution, 11-Cross-section view of the transition point of the liquid outlet of the high-speed equalizing liquid supply spinneret, 12-Fluid feed assembly, 13-Air inlet, 14-Gas regulating assembly, 15-Air outlet shell, 16-Wall-attached guide-directional pressurization structure, 17-Baffle plate, 18-Adjustment hole, 19-Annular guide protrusion, 20-Conical converging outer wall, 21-Radial air outlet gap, 22-Liquid outlet needle, 23-High voltage power supply, 24-Solution channel tube. Detailed Implementation

[0022] Overall, this invention relates to a high-speed electrospinning method based on inorganic molecular chain solutions. By modifying metal alkoxide monomers to achieve linear linkage, and then sequentially subjecting them to hydrolysis-condensation, chain extension, and UV-responsive end-capping reactions, linear inorganic molecular chains with different degrees of polymerization are obtained. High- and low-degree-of-polymerization molecular chain solutions are compounded to prepare a high-solids-content inorganic molecular chain spinning solution with a bimodal molecular weight distribution. Furthermore, cationic components are introduced to regulate the conductivity and rheological properties of the solution, thereby improving the spinnability of the spinning solution. During the spinning process, the spinning solution is first uniformly and stably transported by a high-speed, pressure-equalizing spinneret, and then fed into a wall-mounted, flow-guided, and pressurized nozzle for spinning. Under the influence of an electrostatic field and a high-speed thin-layer airflow, the spinning jet is ejected at high speed in the stable region and stretched and refined in the whipping region, thereby obtaining precursor nanofibers. These precursor nanofibers are then calcined at high temperature to obtain ceramic nanofiber materials with diameters of 50–500 nm, and the spinning rate per nozzle can reach 2–10 kg / day.

[0023] The specific steps are as follows: S1. A bidentate linker is slowly added to a metal alkoxide monomer solution to act as an intermediate for linearly linking two metal alkoxide monomers. Then, a bidentate stabilizer is used to replace the remaining active groups of the metal alkoxide to form a linear pre-coordinated framework. Subsequently, an inorganic acid and water are added to the solution to induce a hydrolysis-condensation reaction, forming a low-polymerization-degree linear inorganic molecular chain. Then, a chain extender is added to extend the low-polymerization-degree linear inorganic molecular chain. A UV-responsive end-capping agent is further added, and UV light irradiation is used to end the linear inorganic long chain, thereby controlling the degree of polymerization of the molecular chain and obtaining linear inorganic molecular chains with different degrees of polymerization. S2. Using the high-polymerization-degree and low-polymerization-degree molecular chains prepared in S1, spinning solutions are prepared separately, and the two solutions are mixed in a certain proportion to obtain a high-solids-content inorganic long-chain spinning solution with a high / low molecular weight bimodal distribution. Then, cationic components are introduced into the solution system to regulate the conductivity and specific viscosity parameters of the spinning solution, thereby improving the spinnability of the spinning solution. S3. The linear inorganic long-chain spinning solution prepared in S2 is transported to the high-speed uniform pressure supply spinneret 1, and then passes through the liquid distribution hole 4, the baffle plate 5, the liquid supply buffer chamber 6, and the transport channel 7 in sequence, and is introduced into the wall-mounted guide-directional pressurization nozzle 2. At the same time, the airflow is sent into the nozzle through the air inlet 13. The linear inorganic long-chain spinning solution is spun under the action of the electrostatic field and the air field dual force field. The airflow changes its flow direction under the action of the annular guide protrusion 19, so that the ejection direction is tangent to the surface of the Taylor cone, thereby driving the jet to be ejected at high speed in the stable region and rapidly dissipated in the whipping region. In addition, the addition of cationic components in the spinning solution increases the solution charge, thereby enhancing the whipping and stretching effect of the spinning jet in the whipping region, and the precursor nanofiber material is obtained. S4. The precursor nanofibers prepared in S3 are calcined at high temperature to obtain ceramic nanofiber materials with uniform diameter. The high-speed pressure equalizing spinneret 1 mainly includes an inlet 3, a distribution hole 4, a baffle plate 5, and a supply buffer chamber 6. The inlet 3 is located on both sides of the spinneret 1, and the distribution hole 4 is located on the baffle plate 5. The spinning solution enters through the inlet 3 and fills the supply buffer chamber 6, then flows into the upper chamber through the distribution hole 4, and is sequentially transported through each stage of the structure. Through the above-mentioned multi-stage diversion and equalization effect, the spinning solution pressure at different locations inside the spinneret is kept consistent, thereby achieving uniform and high-speed supply of solution to each nozzle. The core components of the wall-mounted guide-directional pressurization nozzle 2 include a gas regulating component 14 and a wall-mounted guide-directional pressurization structure 16. The gas regulating component 14 consists of a baffle plate 17 and regulating holes 18 embedded in the baffle plate 17. The regulating holes 18 are arranged in a ring shape, with a decreasing lateral gradient in diameter. When gas flows through the regulating component, the gradient regulating holes 18 distribute and guide the airflow, ensuring uniform flow in the axial direction. The wall-mounted guide-directional pressurization structure 16 is located at the bottom end of the outlet housing 15 and consists of an annular guide protrusion 19. It is composed of a conical converging outer wall 20, and a radial air outlet gap 21 is formed between the two; the width of the radial air outlet gap 21 gradually decreases, so that the airflow is accelerated in the nozzle area and forms a high-speed thin-layer airflow; the outer wall contour of the annular guide protrusion 19 first increases and then decreases along the nozzle axis, and the high-speed thin-layer airflow gradually changes direction during the flow along the wall, and finally becomes tangent to and parallel to the surface of the jet Taylor cone, thereby generating directional traction on the jet and promoting the jet to achieve high-speed injection in the stable region; after entering the whipping region, the high-speed thin-layer airflow dissipates rapidly and does not affect the stretching and refinement of the jet.

[0024] In specific implementations, the metal alkoxide is selected from indium isopropoxide, indium triethoxy, indium tert-butoxide, titanium tetraethanol, titanium isobutoxide, titanium n-propoxide, titanium n-butoxide, titanium tetramethanol, titanium tert-butoxide, titanium isooctanol, titanium tetrapentoxide, titanium isopropoxide, zirconium tetraethanol, zirconium tetrapropoxide, zirconium n-propoxide, zirconium isobutoxide, zirconium tert-butoxide, zirconium n-butoxide, zirconium tetrapentoxide, aluminum n-butoxide, aluminum trimethoxy, and aluminum tri-propoxide. Aluminum, aluminum isopropoxide, aluminum sec-butoxide, aluminum triethanolamine, aluminum tert-butoxide, tin n-propoxide, tin n-butoxide, tin tetramethanol, tin tert-butoxide, tin tetraethanolamine, tin isobutoxide, tin isopropoxide, tin tetrapentanol, gallium isopropoxide, gallium triethoxy, gallium n-butoxide, gallium tert-butoxide, hafnium tetramethanol, hafnium tetraethanolamine, hafnium n-propoxide, hafnium isopropoxide, hafnium n-butoxide, hafnium isobutoxide, hafnium tert-butoxide, hafnium tetrapentanol, tantalum isopropoxide, tantalum n-butoxide The following are selected from one or more combinations of niobium isopropoxide and niobium n-butoxide: the bidentate linker is selected from one or more of p-phenylenediamine, 1,4-naphthyldiamine, 1,4-benzenediol, or terephthalic acid; the bidentate stabilizer is selected from one or more of ethylenediamine, acetylacetone, and tetramethylethylenediamine; the chain extender is selected from one or more of diisopropoxydiacetylacetonitrile, diisopropyl bis(ethyl acetoacetate)titanate, di(diethylcitrate)dipropoxidezirconium, di(ethyl acetoacetate)diisopropoxyaluminate, titanium dichlorocerocene, zirconium dichlorocerocene, hafnium dichlorocerocene, molybdenum dichlorocerocene, vanadium dichlorocerocene, and niobium dichlorocerocene; the UV-responsive end-capping agent is selected from one or more of 4-azidobenzoic acid, 3-azidopropyltrimethoxysilane, and 1,3-dioxopentanepropyltrimethoxysilane.

[0025] In specific implementation, the degree of polymerization of the low-polymerization-degree linear inorganic long chain is 200~1000, and the degree of polymerization of the high-polymerization-degree linear inorganic long chain is 2000~5000; the solid content of the inorganic molecular chain solution is 30~70wt%, the viscosity is 10~10000mPa·s, the electrical conductivity is 0.1~1000μS / cm, the surface tension is 30~120mN / m, and the specific viscosity is 0.3~0.9; In specific implementation, the high-speed pressure equalizing spinneret 1 is internally equipped with an inlet 3, a distribution hole 4, a baffle plate 5, a supply buffer chamber 6, a conveying channel 7, and an outlet 8, wherein the distribution hole 4 is located on the baffle plate 5. After the spinning solution enters the spinneret through the inlet 3, it is conveyed upwards step by step through the distribution hole 4 located on the baffle plate 5, and then collects at the upper end of the spinneret and enters the conveying channel 7. Subsequently, it is supplied to each nozzle installed below through the outlet 8. Through the above structural arrangement, the spinneret can uniformly distribute the spinning solution under high-speed supply conditions and achieve stable and high-speed supply to each nozzle. The high-speed pressure equalizing spinneret 1 is made of a corrosion-resistant material, which can be selected from one or more of stainless steel, titanium alloy, aluminum alloy, nickel-based alloy, and high-strength engineering resin. The baffle plates 5 are distributed at intervals from bottom to top inside the spinneret, and a supply buffer cavity 6 is formed between two baffle plates 5. The distributing holes 4 on each baffle plate 5 are arranged at intervals along the spinneret axial direction, and their number increases progressively from bottom to top. The diameter of the distributing holes 4 is 0.1~2.0mm, and the total number is 2~200. The shape of the distributing holes 4 can be selected from one of circular, elliptical, rhomboid, or slit shape to adapt to spinning solutions with different rheological properties.

[0026] In specific implementation, the nozzle 2 adopts a split modular structure, including a fluid feed assembly 12 and an air outlet shell 15, which are independent of each other and sealed together to form a solution channel pipe 24 and an airflow channel that are isolated from each other inside the nozzle; wherein, the solution channel pipe 24 is arranged along the axis of the nozzle, and the airflow channel is distributed in a ring around the solution channel pipe 24. The fluid feed assembly 12 is used to transport the spinning solution and is connected to a liquid outlet needle. An air inlet 13 is provided on the needle, which is connected to the gas regulating assembly 14 to regulate the gas entering the nozzle. A wall-mounted guide-directional pressurization structure 16 is provided at the bottom of the air outlet shell 15 to guide and accelerate the ejected airflow. An elastic seal is provided at the connection between the fluid feed assembly 12 and the air outlet shell 15 to ensure the sealing of the solution channel pipe 24 and the airflow channel and the stability of the overall nozzle structure while enabling quick assembly and disassembly.

[0027] The thickness of the gas regulating component 14 is 0.1~0.4mm, and the diameter of the regulating hole 18 is 0.3~0.9mm; the axial length of the annular guiding protrusion 19 in the wall-attached flow guiding-directional pressurization structure 16 is 1.5~3.0 times the width of the radial air outlet gap 21, and the radial thickness of the annular guiding protrusion 19 is 0.2~1 times the outer diameter of the liquid outlet needle; the conical converging outer wall 20 is configured as a converging structure along the axial direction of the nozzle, and its converging half angle relative to the nozzle axis is 3~20°, and the minimum radius of curvature of the conical converging outer wall 20 is 0.3~1.2 times the outer diameter of the liquid outlet needle; the radial width of the radial air outlet gap 21 is 0.1~1mm.

[0028] The nozzle 2 is prepared using one or more of high-strength engineering plastics, solvent-resistant resin materials, or ceramic matrix composites as raw materials; In practice, the air inlet is sealed to the air supply pipeline via a plug-in adapter; the air supply pipeline is equipped with an interface for monitoring air pressure or airflow parameters to monitor the air supply status in real time, and the gas flow and air pressure are regulated by a gas regulating valve installed on the air supply pipeline to achieve stable and controllable airflow parameters during nozzle operation.

[0029] In specific implementation, the dispensing needle is a replaceable needle assembly and has at least the following characteristics: the needle and the inlet assembly are detachably fixed by a threaded connection or a snap-fit ​​connection to meet the needs of quick replacement and maintenance; the needle has a variety of different inner diameter specifications, and its model is selected from one or more of 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, and 25G to adapt to inorganic molecular chain solutions with different rheological properties; the needle material is selected from stainless steel or solvent-resistant metal alloys, and the solvent-resistant metal alloys include one or more of Hastelloy, Monel, or titanium alloys.

[0030] In specific implementation, a cationic component that can adsorb onto the oxygen sites in the metal-oxygen bond is introduced into the inorganic molecular chain solution. The cationic component is introduced in the form of a compound and is selected from one or more of the following: hydrochloric acid, phosphoric acid, formic acid, acetic acid, propionic acid, butyric acid, lactic acid, oxalic acid, malonic acid, succinic acid, citric acid, sodium chloride, lithium chloride, potassium chloride, magnesium chloride, calcium chloride, barium chloride, zinc chloride, ferric chloride, sodium carbonate, potassium carbonate, silver nitrate, copper nitrate, lithium bromide, tetrabutylammonium bromide, tetrabutylammonium chloride, and tetraethylammonium chloride. This improves the jet's charge characteristics and reduces electrostatic adsorption between inorganic molecular chains, thereby enhancing the jet's whipping and refining ability in an electrostatic field.

[0031] In practice, by adjusting the output voltage to -120~120kV, the airflow velocity to 0~100m / s, the spinning solution injection rate to 10~200mL / h, the receiving distance between the needle and the receiving device to 30~50cm, the spinning environment temperature to 25~35℃, and the environmental humidity to 20~90%, the spinning jet can achieve high-speed fiber formation and refinement.

[0032] In practice, this technology significantly improves the spinning rate and refines the diameter of nanofibers, producing fibers with a diameter of 50~500nm and a single-nozzle spinning rate of 2~10kg / day.

[0033] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. Component models, material names, connection structures, control methods, algorithms, and other features not explicitly described in this technical solution are considered common technical features disclosed in the prior art.

[0034] Example 1: This embodiment provides a high-speed electrospinning method based on inorganic molecular chain solutions.

[0035] See Figures 1 to 9 In this embodiment, the high-speed pressure equalizing spinneret 1 has an inlet 3 and an outlet 8 on its main body. The interior of the high-speed pressure equalizing spinneret 1 includes a distribution hole 4, a baffle plate 5, a supply buffer chamber 6, and a delivery channel 7. The baffle plates 5 are spaced apart from bottom to top inside the high-speed pressure equalizing spinneret 1, and a supply buffer chamber 6 is formed between adjacent baffle plates 5. The distribution holes 4 are located on the baffle plates 5. The distribution holes 4 on each baffle plate 5 extend along the spinneret... The spinnerets are arranged axially at intervals, and the number of distributing holes 4 increases progressively from bottom to top in the direction of the baffle plate 5; the inlet 3 is located on both sides of the main body of the high-speed equalizing liquid supply spinneret 1, and the inlet 3 is connected to the bottom liquid supply buffer chamber 6; the beginning of the conveying channel 7 is connected to the distributing hole 4 on the top baffle plate 5, and the end of the conveying channel 7 is connected to the outlet 8; the outlet 8 is located at the bottom of the high-speed equalizing liquid supply spinneret 1.

[0036] In practice, the spinning solution is introduced into the spinneret through the inlet 3, and then conveyed upwards step by step through the distribution holes 4 on the baffle plate 5. It is collected at the upper end of the high-speed pressure equalizing spinneret 1 and enters the conveying channel 7. Then, it is supplied to each wall-mounted guide-directional pressure boosting nozzle 2 installed below it through the outlet 8. Through the above structural arrangement, the spinneret can evenly distribute the spinning solution under high-speed liquid supply conditions and achieve stable and high-speed liquid supply to each nozzle.

[0037] In specific implementation, each wall-mounted guide-directional pressurization nozzle 2 adopts a split modular structure, and each wall-mounted guide-directional pressurization nozzle 2 includes a fluid feed assembly 12 and an air outlet shell 15; In specific implementation, the fluid feeding assembly 12 includes a fluid feeding assembly outer tube body, a solution channel tube 24 disposed inside the fluid feeding assembly outer tube body and arranged axially, and a liquid outlet needle 22 connected to the end of the solution channel tube 24. The air outlet shell 15 is threadedly connected to the end of the fluid feeding assembly outer tube body. An annular airflow channel is formed between the outer wall of the solution channel tube 24 and the liquid outlet needle 22 and the inner wall of the fluid feeding assembly outer tube body and the inner wall of the air outlet shell 15. The upper end of the fluid feeding assembly outer tube body is provided with an external thread interface. The bottom surface of the body of the high-speed equalizing liquid supply spinneret 1 is provided with multiple internal thread interfaces that match the external thread interface at the position corresponding to the liquid outlet 8. The fluid feeding assembly outer tube body is threadedly connected to the bottom surface of the body of the high-speed equalizing liquid supply spinneret 1. In a specific implementation, a gas regulating component 14 is provided in the airflow channel. The gas regulating component 14 includes a baffle plate 17 and a plurality of regulating holes 18 disposed thereon. The plurality of regulating holes 18 are arranged in a ring around the outside of the solution channel tube 24, and their diameter is set in a gradient decreasing along the transverse direction of the baffle plate 17, for the purpose of equalizing and distributing the incoming airflow.

[0038] In specific implementation, the bottom end of the air outlet shell 15 is provided with a wall-mounted flow guiding-directional pressurization structure 16. The wall-mounted flow guiding-directional pressurization structure 16 includes an annular flow guiding protrusion 19 and a conical converging outer wall 20. The annular flow guiding protrusion 19 is arranged around the outside of the liquid outlet needle 22. A radially narrowing air outlet gap 21 is formed between the annular flow guiding protrusion 19 and the conical converging outer wall 20. The conical converging outer wall 20 is used to accelerate the airflow to form a high-speed thin-layer airflow. The annular flow guiding protrusion 19 is used to guide the flow direction of the high-speed thin-layer airflow so that it is tangent to the Taylor cone surface of the spinning solution ejected from the liquid outlet needle 22 when it is ejected.

[0039] In this embodiment, the high-speed pressure equalizing spinneret 1 is made of corrosion-resistant and high-pressure-resistant stainless steel. The number of the distributing holes 4 are 2, 4, 8, 16, 32, and 64 respectively, and the diameter of the distributing holes is 0.5 mm.

[0040] The nozzle adopts a split modular design, and the material selection and processing requirements for each component are as follows: Fluid feed assembly 12: made of polyetheretherketone material and 3D printed; solution channel tube 24 with an inner diameter of 4 mm; gas regulating assembly 14 with a thickness of 0.2 mm; regulating hole 18 with diameters of 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, 0.65 mm and 0.7 mm along the transverse direction. The exhaust shell 15 is made of polyetheretherketone (PEEK) material and is 3D printed. The width of the annular airflow channel is 1 mm. The specific parameters of the wall-mounted guide-directional pressurization structure 16 are as follows: the axial length of the annular guide protrusion 19 is 3 times the width of the radial exhaust gap 21; the radial thickness of the annular guide protrusion 19 is 0.8 times the outer diameter of the liquid outlet needle; the converging half-angle of the tapered converging outer wall 20 relative to the nozzle axis is 10°, the minimum radius of curvature is 0.6 times the outer diameter of the liquid outlet needle, and the radial width of the radial exhaust gap 21 is 0.6 mm.

[0041] This embodiment is based on a high-speed electrospinning method using inorganic molecular chain solutions. The specific steps are as follows: p-Phenylenediamine was diluted with dichloromethane at a mass ratio of 1:5 and then slowly added dropwise to titanium isopropoxide under stirring at 500 r / min, allowing p-Phenylenediamine to act as an intermediate to link the titanium alkoxide monomer. Subsequently, acetylacetone was added to the resulting reaction system as a stabilizer to replace the remaining active groups in the titanium alkoxide, forming a linear pre-coordinated framework for the titanium alkoxide. The mass percentages of titanium isopropoxide, p-Phenylenediamine, dichloromethane, and acetylacetone in the reaction system were 30 wt%, 10 wt%, 50 wt%, and 10 wt%, respectively.

[0042] The pH of the reaction system was adjusted to 3 by adding hydrochloric acid, and deionized water was added in an amount equal to 15% of the mass of titanium isopropoxide. The reaction was then stirred at 50 °C for 4 h to promote hydrolysis and polycondensation, yielding linear titanium oxide molecular chains with a degree of polymerization of 50. Diisopropoxydiacetylacetonate titanium was then added as a chain extender to the linear titanium oxide molecular chain system, and 1,3-dioxopentacyclopropyltrimethoxysilane was further added as a UV-responsive end-capping agent. The degree of chain extension was controlled by adjusting the UV irradiation, resulting in low-degree-of-polymerization and high-degree-of-polymerization linear titanium oxide molecular chains. The low-degree-of-polymerization linear titanium oxide molecular chain had a degree of polymerization of 300 and a molecular weight of 90,000; the high-degree-of-polymerization linear titanium oxide molecular chain had a degree of polymerization of 2000 and a molecular weight of 600,000.

[0043] The low-polymerization-degree linear titanium dioxide molecular chain liquid with a polymerization degree of 300 and the high-polymerization-degree linear titanium dioxide molecular chain liquid with a polymerization degree of 2000, prepared above, were used to prepare spinning solutions. The spinning solutions were prepared using a mixed solvent in which the mass ratio of methanol, diethyl ether, and N,N-dimethylformamide was 80:15:5. The two spinning solutions were then mixed at a mass ratio of low-polymerization-degree spinning solution:high-polymerization-degree spinning solution = 1:4, and a compound spinning solution with a total solid content of 40 wt% was prepared using the mixed solvent. Its viscosity was measured to be 400 mPa·s. Lithium chloride was then added to the compound spinning solution at a mass of 0.5 wt% of the spinning solution. The final spinning solution had a conductivity of 180 μS / cm, a surface tension of 55 mN / m, and a specific viscosity of 0.5.

[0044] Select a 20G replaceable stainless steel dispensing needle and set the electrospinning parameters as follows: voltage 45kV, spinning solution supply rate 100mL / h, receiving distance 35cm, nozzle gas velocity 16m / s, ambient temperature 25℃, and relative humidity 35%. The spinning solution is delivered to the spinneret, and after multi-stage pressure equalization, it is delivered to the nozzle. Under the guidance of the annular guide protrusion, the airflow is tangential to the surface of the Taylor cone, driving the jet to be ejected at high speed to obtain precursor nanofibers. Subsequently, after high-temperature calcination, titanium oxide ceramic nanofibers are obtained.

[0045] The results showed that the prepared titanium oxide ceramic nanofibers had no obvious fractures or bead-like defects, and the fiber surface was smooth. The average diameter of the obtained ceramic nanofibers was 50~200nm. Under the above process conditions, the fiber yield per nozzle was about 2.5kg / day.

[0046] Example 2: Based on Example 1, this example provides a high-speed electrospinning method based on inorganic molecular chain solution, the specific steps of which are as follows: A diluted solution of 1,4-naphthyldiamine was prepared with dichloromethane at a mass ratio of 1:6. This diluted solution was then slowly added dropwise to aluminum isopropoxide under stirring at 300 r / min, allowing 1,4-naphthyldiamine to act as an intermediate linking the aluminum alkoxide monomer. Subsequently, ethylenediamine was added to the resulting reaction system as a stabilizer to replace the remaining active groups in the aluminum alkoxide, forming a linear pre-coordinated framework for the aluminum alkoxide. The mass percentages of aluminum isopropoxide, 1,4-naphthyldiamine, dichloromethane, and ethylenediamine in the reaction system were 32 wt%, 8 wt%, 48 wt%, and 12 wt%, respectively.

[0047] The pH of the reaction system was adjusted to 3 by adding hydrochloric acid, and deionized water was added at 12% of the mass of aluminum isopropoxide. The reaction was then stirred at 30 °C for 4 h to promote hydrolysis and polycondensation, yielding linear alumina molecular chains with a degree of polymerization of 80. Ethyl acetoacetate diisopropoxyaluminate was then added as a chain extender to the linear alumina molecular chain system, and 4-azidobenzoic acid was further added as a UV-responsive end-capping agent. The degree of chain extension was controlled by adjusting the UV irradiation, resulting in low-degree-of-polymerization and high-degree-of-polymerization linear alumina molecular chains. The low-degree-of-polymerization linear alumina molecular chain had a degree of polymerization of 900 and a molecular weight of 160,000; the high-degree-of-polymerization linear alumina molecular chain had a degree of polymerization of 3200 and a molecular weight of 580,000.

[0048] The low-polymerization-degree linear alumina molecular chain liquid with a polymerization degree of 900 and the high-polymerization-degree linear alumina molecular chain liquid with a polymerization degree of 3200, prepared above, were used to prepare spinning solutions. The spinning solutions were prepared using a mixed solvent in which the mass ratio of methanol, diethyl ether, and N,N-dimethylformamide was 75:20:5. The two spinning solutions were then mixed at a mass ratio of low-polymerization-degree spinning solution to high-polymerization-degree spinning solution of 1:3, and a compound spinning solution with a total solid content of 45 wt% was prepared using the mixed solvent. Its viscosity was measured to be 430 mPa·s. Potassium chloride was then added to the compound spinning solution at a mass of 0.4 wt% of the spinning solution. The final spinning solution had a conductivity of 100 μS / cm, a surface tension of 60 mN / m, and a specific viscosity of 0.6.

[0049] Select a 21G replaceable stainless steel dispensing needle and set the electrospinning parameters as follows: voltage 40 kV, spinning solution supply rate 90 mL / h, receiving distance 30 cm, nozzle gas velocity 18 m / s, ambient temperature 25 ℃, and relative humidity 30%. The spinning solution is delivered to the spinneret, and after multi-stage pressure equalization, it is delivered to the nozzle. Under the guidance of the annular guide protrusion, the airflow is tangential to the surface of the Taylor cone, driving the jet to be ejected at high speed to obtain precursor nanofibers. Subsequently, after high-temperature calcination, alumina ceramic nanofibers are obtained.

[0050] The results showed that the prepared alumina ceramic nanofibers had no obvious fractures or bead-like defects, and the fiber surface was smooth. The average diameter of the obtained ceramic nanofibers was 100–350 nm. Under the above process conditions, the fiber yield per nozzle was about 2.5 kg / day.

[0051] Example 3: Based on Example 1, this example provides a high-speed electrospinning method based on inorganic molecular chain solution, the specific steps of which are as follows: Terephthalic acid was diluted with toluene at a mass ratio of 1:10 to prepare a dilution solution, which was then slowly added dropwise to zirconium tert-butoxide under stirring at 300 r / min, allowing terephthalic acid to act as an intermediate for linking the zirconium alkoxide monomer. Subsequently, acetylacetone was added to the resulting reaction system as a stabilizer to replace the remaining active groups in the zirconium alkoxide, forming a linear pre-coordinated framework for the zirconium alkoxide. The mass percentages of zirconium tert-butoxide, terephthalic acid, toluene, and acetylacetone in the reaction system were 30 wt%, 6 wt%, 60 wt%, and 4 wt%, respectively.

[0052] The pH of the reaction system was adjusted to 3 by adding hydrochloric acid, and deionized water was added at 12% of the mass of zirconium tert-butoxide. The reaction was then stirred at 35 °C for 5 h to promote hydrolysis-condensation polymerization, yielding linear zirconium oxide molecular chains with a degree of polymerization of 60. Then, bis(diethylcitrate)dipropoxide zirconium was added as a chain extender to the above linear zirconium oxide molecular chain system for chain extension, and 3-azidopropyltrimethoxysilane was further added as a UV-responsive end-capping agent. By controlling UV irradiation, the degree of chain extension was regulated, resulting in low-degree-of-polymerization and high-degree-of-polymerization linear zirconium oxide molecular chains. The obtained low-degree-of-polymerization linear zirconium oxide molecular chain had a degree of polymerization of 600 and a molecular weight of 160,000; the obtained high-degree-of-polymerization linear zirconium oxide molecular chain had a degree of polymerization of 2800 and a molecular weight of 720,000.

[0053] The low-polymerization-degree linear zirconia molecular chain liquid with a polymerization degree of 600 and the high-polymerization-degree linear zirconia molecular chain liquid with a polymerization degree of 2800, prepared above, were used to prepare spinning solutions. The spinning solutions were prepared using a mixed solvent in which the mass ratio of methanol, diethyl ether, and N,N-dimethylformamide was 78:17:5. The two spinning solutions were then mixed at a mass ratio of low-polymerization-degree spinning solution:high-polymerization-degree spinning solution = 1:4, and a compound spinning solution with a total solid content of 50 wt% was prepared using the mixed solvent. Its viscosity was measured to be 480 mPa·s. Sodium chloride was then added to the compound spinning solution at a mass of 0.5 wt% of the spinning solution. The final spinning solution had a conductivity of 120 μS / cm, a surface tension of 70 mN / m, and a specific viscosity of 0.7.

[0054] Select a 22G replaceable stainless steel dispensing needle and set the electrospinning parameters as follows: voltage 50 kV, spinning solution supply rate 95 mL / h, receiving distance 35 cm, nozzle gas velocity 20 m / s, ambient temperature 25 ℃, and relative humidity 35%. The spinning solution is delivered to the spinneret, and after multi-stage pressure equalization, it is delivered to the nozzle. Under the guidance of the annular guide protrusion, the airflow is tangential to the surface of the Taylor cone, driving the jet to be ejected at high speed to obtain precursor nanofibers. Subsequently, after high-temperature calcination, zirconia ceramic nanofibers are obtained.

[0055] The results showed that the prepared zirconia ceramic nanofibers had no obvious fractures or bead-like defects, and the fiber surface was smooth. The average diameter of the obtained ceramic nanofibers was 50-350 nm. Under the above process conditions, the fiber yield per nozzle was about 3 kg / day.

[0056] Example 4: This embodiment provides a high-speed electrospinning method based on inorganic molecular chain solutions, the specific steps of which are as follows: Titanium isopropoxide, aluminum isopropoxide, zirconium tert-butoxide, tin tetraethanolamine, and hafnium isopropoxide were selected as metal alkoxide monomers and prepared into a mixed metal alkoxide solution. p-Phenylenediamine was diluted with dichloromethane at a mass ratio of 1:4 and slowly added dropwise to the mixed metal alkoxide solution under stirring at 400 r / min, allowing p-Phenylenediamine to act as an intermediate to link the different metal alkoxide monomers. Subsequently, acetylacetone was added to the resulting reaction system as a stabilizer to replace the remaining active groups in the metal alkoxides, forming a linear pre-coordinated framework for the polymetallic alkoxide. The mass percentages of the mixed metal alkoxide, p-Phenylenediamine, dichloromethane, and acetylacetone in the reaction system were 35 wt%, 10 wt%, 40 wt%, and 15 wt%, respectively.

[0057] The pH of the reaction system was adjusted to 3 by adding hydrochloric acid, and deionized water was added at 18% of the total mass of the mixed metal alkoxides. The reaction was then stirred at 60 °C for 5 h to promote hydrolysis-condensation reaction, yielding a linear high-entropy oxide molecular chain with a degree of polymerization of 100. Diisopropoxydiacetylacetonate titanium was then added as a chain extender to the above linear high-entropy oxide molecular chain system, and 4-azidobenzoic acid was further added as a UV-responsive end-capping agent. The degree of chain extension was controlled by adjusting the UV irradiation, resulting in low-degree-of-polymerization and high-degree-of-polymerization linear high-entropy oxide molecular chains. The low-degree-of-polymerization linear high-entropy oxide molecular chain had a degree of polymerization of 1200 and a molecular weight of 300,000; the high-degree-of-polymerization linear high-entropy oxide molecular chain had a degree of polymerization of 3600 and a molecular weight of 900,000.

[0058] The low-polymerization-degree linear high-entropy oxide molecular chain liquid with a polymerization degree of 1200 and the high-polymerization-degree linear high-entropy oxide molecular chain liquid with a polymerization degree of 3600 were prepared into spinning solutions using a mixed solvent. The spinning solutions were prepared using a mixed solvent in which the mass ratio of methanol, diethyl ether, and N,N-dimethylformamide was 70:20:10. The two spinning solutions were then mixed at a mass ratio of low-polymerization-degree spinning solution to high-polymerization-degree spinning solution of 1:4, and a compound spinning solution with a total solid content of 55 wt% was prepared using the mixed solvent. Its viscosity was measured to be 500 mPa·s. Lithium chloride was then added to the compound spinning solution at a mass of 0.6 wt% of the spinning solution. The final spinning solution had a conductivity of 140 μS / cm, a surface tension of 80 mN / m, and a specific viscosity of 0.75.

[0059] Select a 21G replaceable stainless steel dispensing needle and set the electrospinning parameters as follows: voltage 55 kV, spinning solution supply rate 100 mL / h, receiving distance 38 cm, nozzle gas velocity 22 m / s, ambient temperature 25 ℃, and relative humidity 35%. The spinning solution is delivered to the spinneret, and after multi-stage pressure equalization, it is delivered to the nozzle. Under the guidance of the annular guide protrusion, the airflow is tangential to the surface of the Taylor cone, driving the jet to be ejected at high speed to obtain precursor nanofibers. Subsequently, after high-temperature calcination, high-entropy oxide ceramic nanofibers are obtained.

[0060] The results show that the obtained high-entropy oxide ceramic nanofibers have good continuity, smooth surface, and no bead-like defects. The average diameter of the ceramic nanofibers is 50–300 nm. Under the above process conditions, the fiber yield per nozzle is about 3.5 kg / day.

[0061] Example 5: As a specific example of the present invention, after protonation treatment of the silicon source, linear inorganic molecular chains can also be formed, which can then be further extended, compounded, spun, and fiberized. The silicon source is selected from one or more combinations of tetraethyl orthosilicate, tetra-n-propoxysilane, tetra-n-butoxysilane, vinyltriethoxysilane, or trimethylsilyl acetate. This embodiment uses tetraethyl orthosilicate as an example, and the specific steps are as follows: A silanol solution with pH=1 and a tetraethyl orthosilicate content of 75wt% was prepared by mixing hydrochloric acid, anhydrous ethanol and tetraethyl orthosilicate.

[0062] p-Phenylenediamine was diluted with dichloromethane at a mass ratio of 1:5 and then slowly added dropwise to tetraethyl orthosilicate under stirring at 600 r / min, allowing p-Phenylenediamine to act as an intermediate for linking the silanolate monomer. Subsequently, ethylenediamine was added to the resulting reaction system as a stabilizer to replace the remaining active groups in the silanolate, forming a linear pre-coordinated framework for the silanolate. The mass percentages of tetraethyl orthosilicate, p-Phenylenediamine, dichloromethane, and ethylenediamine in the reaction system were 30 wt%, 10 wt%, 50 wt%, and 10 wt%, respectively.

[0063] The pH of the reaction system was adjusted to 3 by adding hydrochloric acid, and deionized water was added in an amount equal to 18% of the mass of tetraethyl orthosilicate. The reaction was then stirred at 35 °C for 6 h to promote hydrolysis-condensation reaction, yielding linear silica molecular chains with a degree of polymerization of 100. Diisopropyl bis(ethyl acetoacetate) titanate was then added to the linear silica molecular chain system as a chain extender, and 3-azidopropyltrimethoxysilane was further added as a UV-responsive end-capping agent. The degree of chain extension was controlled by adjusting the UV irradiation, resulting in low-degree-of-polymerization and high-degree-of-polymerization linear silica molecular chains. The low-degree-of-polymerization linear silica molecular chain had a degree of polymerization of 1200 and a molecular weight of 180,000; the high-degree-of-polymerization linear silica molecular chain had a degree of polymerization of 3200 and a molecular weight of 500,000.

[0064] The low-polymerization-degree linear silica molecular chain liquid with a polymerization degree of 1200 and the high-polymerization-degree linear silica molecular chain liquid with a polymerization degree of 3200, prepared above, were used to prepare spinning solutions. The spinning solutions were prepared using a mixed solvent in which the mass ratio of methanol, diethyl ether, and N,N-dimethylformamide was 75:20:5. The two spinning solutions were then mixed at a mass ratio of low-polymerization-degree spinning solution:high-polymerization-degree spinning solution = 1:3, and a compound spinning solution with a total solid content of 50 wt% was prepared using the mixed solvent. Its viscosity was measured to be 460 mPa·s. Magnesium chloride was then added to the compound spinning solution at a mass of 0.5 wt% of the spinning solution. The final spinning solution had a conductivity of 130 μS / cm, a surface tension of 65 mN / m, and a specific viscosity of 0.6.

[0065] Select a 21G replaceable stainless steel dispensing needle and set the electrospinning parameters as follows: voltage 55 kV, spinning solution supply rate 130 mL / h, receiving distance 40 cm, nozzle gas velocity 25 m / s, ambient temperature 25 ℃, and relative humidity 35%. The spinning solution is delivered to the spinneret, and after multi-stage pressure equalization, it is delivered to the nozzle. Under the guidance of the annular guide protrusion, the airflow is tangential to the surface of the Taylor cone, driving the jet to be ejected at high speed to obtain precursor nanofibers. Subsequently, after high-temperature calcination, silica ceramic nanofibers are obtained.

[0066] The results showed that the prepared silica ceramic nanofibers had no obvious fractures or bead-like defects, and the fiber surface was smooth. The average diameter of the obtained ceramic nanofibers was 50–350 nm. Under the above process conditions, the fiber yield per nozzle was about 4 kg / day.

[0067] The above embodiments are merely preferred embodiments of the present invention, used to illustrate the technical solutions of the present invention, and are not intended to limit the scope of protection of the present invention. For those skilled in the art, various modifications, substitutions, and improvements can be made to the above embodiments without departing from the concept and spirit of the present invention, and all such modifications, substitutions, and improvements should fall within the scope of protection of the present invention.

Claims

1. A high-speed electrospinning method based on an inorganic molecular chain solution, characterized in that, Includes the following steps: S1. A linear-rigid bidentate linker is added to a metal alkoxide monomer solution to linearly link the monomers. Then, a bidentate stabilizer is added to form a linear pre-coordinated framework. Subsequently, acid and water are added to perform hydrolysis and polycondensation to obtain low-polymerization-degree linear inorganic molecular chains. Then, a chain extender is added to extend the chain, and a UV-responsive end-capping agent is added to end the chain under UV irradiation, thereby controlling the degree of polymerization of the molecular chains and obtaining linear inorganic molecular chains with different degrees of polymerization. S2. Prepare spinning solutions for the high-polymerization degree and low-polymerization degree molecular chains obtained in S1 respectively, and mix the two solutions to obtain a high-solids content spinning solution with a bimodal molecular weight distribution. Introduce cationic components into the mixed solution to regulate its solution properties. S3. The spinning solution prepared in step S2 is transported to the high-speed pressure equalizing spinneret (1). After pressure equalization through the multi-level liquid distribution holes (4) and the liquid supply buffer chamber (6) inside the high-speed pressure equalizing spinneret (1), it is introduced into the wall-mounted guide-directional pressurizing nozzle (2). At the same time, airflow is introduced into the air inlet (13) of the wall-mounted guide-directional pressurizing nozzle (2). Under the combined action of the electrostatic field and the high-speed airflow tangent to the surface of the Taylor cone after being guided by the annular guide protrusion (19) inside the nozzle, the spinning solution jet achieves high-speed jetting in the stable region and is fully stretched and refined in the whipping region under the enhanced charging effect of the cationic component, thereby obtaining the precursor nanofiber. S4. High-temperature calcination: The precursor nanofibers obtained in S3 are subjected to high-temperature calcination to obtain ceramic nanofiber materials.

2. The high-speed electrospinning method based on an inorganic molecular chain solution according to claim 1, characterized in that, In S1, the metal alkoxide is selected from indium isopropoxide, indium triethoxy, indium tert-butoxide, titanium tetraethanol, titanium isobutoxide, titanium n-propoxide, titanium n-butoxide, titanium tetramethanol, titanium tert-butoxide, titanium isooctanol, titanium tetrapentoxide, titanium isopropoxide, zirconium tetraethanol, zirconium isopropoxide, zirconium n-propoxide, zirconium isobutoxide, zirconium tert-butoxide, zirconium n-butoxide, zirconium tetrapentoxide, aluminum n-butoxide, aluminum trimethoxy, aluminum tri-n-propoxy, aluminum isopropoxide, and aluminum sec-butoxide. One or more combinations of aluminum triethanolamine, aluminum tert-butoxide, tin n-propoxide, tin n-butoxide, tin tetraethanolamine, tin tert-butoxide, tin tetraethanolamine, tin isobutoxide, tin isopropoxide, tin tetrapentanol, gallium isopropoxide, gallium triethoxy, gallium n-butoxide, gallium tert-butoxide, hafnium tetraethanolamine, hafnium tetraethanolamine, hafnium n-propoxide, hafnium isopropoxide, hafnium n-butoxide, hafnium isobutoxide, hafnium tert-butoxide, hafnium tetrapentanol, tantalum isopropoxide, tantalum n-butoxide, niobium isopropoxide, and niobium n-butoxide; The bidental connector is selected from one or more of p-phenylenediamine, 1,4-naphthylenediamine, 1,4-benzenediol, and terephthalic acid; The didentate stabilizer is selected from one or more of ethylenediamine, acetylacetone, and tetramethylethylenediamine; The chain extender is selected from one or more of the following: diisopropoxydiacetylacetonate titanium, bis(ethyl acetoacetate)titanate diisopropyl ester, bis(diethylcitrate)dipropoxide zirconium, (ethyl acetoacetate)diisopropoxyaluminate, titanium dichlorodecene, zirconium dichlorodecene, hafnium dichlorodecene, molybdenum dichlorodecene, vanadium dichlorodecene, and niobium dichlorodecene. The UV-responsive end-capping agent is selected from one or more of 4-azidobenzoic acid, 3-azidopropyltrimethoxysilane, and 1,3-dioxopentanepropyltrimethoxysilane.

3. The high-speed electrospinning method based on an inorganic molecular chain solution according to claim 1, characterized in that, In S1, the degree of polymerization of the low-polymerization-degree linear inorganic long chain is 200~1000, and the degree of polymerization of the high-polymerization-degree linear inorganic long chain is 2000~5000. In S2, the inorganic molecular chain solution has a solid content of 30~70wt%, a viscosity of 10~10000mPa·s, an electrical conductivity of 0.1~1000μS / cm, a surface tension of 30~120mN / m, and a specific viscosity of 0.3~0.

9.

4. The high-speed electrospinning method based on an inorganic molecular chain solution according to claim 1, characterized in that, In S2, the cationic component is introduced in the form of a compound selected from one or more of hydrochloric acid, phosphoric acid, formic acid, acetic acid, propionic acid, butyric acid, lactic acid, oxalic acid, malonic acid, succinic acid, citric acid, sodium chloride, lithium chloride, potassium chloride, magnesium chloride, calcium chloride, barium chloride, zinc chloride, ferric chloride, sodium carbonate, potassium carbonate, silver nitrate, copper nitrate, lithium bromide, tetrabutylammonium bromide, tetrabutylammonium chloride, and tetraethylammonium chloride. The compound is used to improve the jet charging characteristics and reduce the electrostatic adsorption between inorganic molecular chains, thereby enhancing the whipping and refining ability of the jet in the electrostatic field.

5. The high-speed electrospinning method based on an inorganic molecular chain solution according to claim 1, characterized in that, In S3, the main body of the high-speed pressure equalizing liquid supply spinneret (1) is provided with an inlet (3) and an outlet (8), and the interior of the high-speed pressure equalizing liquid supply spinneret (1) is provided with a liquid distribution hole (4), a baffle plate (5), a liquid supply buffer chamber (6), and a conveying channel (7). The barrier plates (5) are distributed from bottom to top inside the high-speed pressure equalizing liquid supply spinneret (1), and a liquid supply buffer cavity (6) is formed between two adjacent barrier plates (5). The liquid separation hole (4) is provided on the barrier plate (5); The liquid distribution holes (4) on each layer of the barrier plate (5) are arranged at intervals along the spinneret axis, and the number of liquid distribution holes (4) increases progressively from bottom to top in the barrier plate (5). The liquid inlet (3) is located on both sides of the main body of the high-speed pressure equalizing liquid supply spinneret (1), and the liquid inlet (3) is connected to the lowest liquid supply buffer chamber (6). The beginning of the conveying channel (7) is connected to the liquid distribution hole (4) on the top layer barrier plate (5), and the end of the conveying channel (7) is connected to the liquid outlet (8). The liquid outlet (8) is located at the bottom of the high-speed pressure equalizing liquid supply spinneret (1); After the spinning solution is introduced into the spinneret through the inlet (3), it is conveyed upward step by step through the distribution hole (4) on the baffle plate (5), and then collected at the upper end of the high-speed pressure equalizing spinneret (1) and entered the conveying channel (7). Subsequently, it is supplied to each wall-mounted guide-directional pressurizing nozzle (2) installed below it through the outlet (8).

6. The high-speed electrospinning method based on an inorganic molecular chain solution according to claim 4, characterized in that, The diameter of the liquid distribution hole (4) is 0.1~2.0mm, and the total number is 2~200. The shape of the liquid distribution hole (4) is selected from one of the following: circular, elliptical, rhomboid, and slit. The high-speed pressure equalizing liquid supply spinneret (1) is made of a corrosion-resistant material, which is selected from one or more of stainless steel, titanium alloy, aluminum alloy, nickel-based alloy, and high-strength engineering resin.

7. The high-speed electrospinning method based on an inorganic molecular chain solution according to claim 5, characterized in that, In S3, each wall-mounted guide-direction pressurizing nozzle (2) adopts a split modular structure, and each wall-mounted guide-direction pressurizing nozzle (2) includes a fluid feed assembly (12) and an air outlet shell (15). The fluid feed assembly (12) includes a fluid feed assembly outer tube body, a solution channel tube (24) disposed inside the fluid feed assembly outer tube body and arranged axially, and a liquid outlet needle (22) connected to the end of the solution channel tube (24). The gas outlet shell (15) is threadedly connected to the end of the fluid feed assembly outer tube body. An annular airflow channel is formed between the outer wall of the solution channel tube (24) and the liquid outlet needle (22) and the inner wall of the fluid feed assembly outer tube body and the inner wall of the gas outlet shell (15). The upper end of the outer tube body of the fluid feed assembly is provided with an external thread interface, and the bottom surface of the body of the high-speed equalizing liquid supply spinneret (1) is provided with multiple internal thread interfaces that match the external thread interface at the position corresponding to the liquid outlet (8). The outer tube body of the fluid feed assembly is threadedly connected to the bottom surface of the body of the high-speed equalizing liquid supply spinneret (1). The airflow channel is provided with a gas regulating component (14), which includes a baffle plate (17) and a plurality of regulating holes (18) thereon. The plurality of regulating holes (18) are arranged in a ring around the outside of the solution channel tube (24), and their diameter is set in a gradient decreasing along the transverse direction of the baffle plate (17) to equalize and distribute the incoming airflow.

8. The high-speed electrospinning method based on an inorganic molecular chain solution according to claim 7, characterized in that, The bottom end of the air outlet shell (15) is provided with a wall-mounted flow guiding-directional pressurization structure (16). The wall-mounted flow guiding-directional pressurization structure (16) includes an annular flow guiding protrusion (19) and a conical converging outer wall (20). The annular flow guiding protrusion (19) surrounds the outside of the liquid outlet needle (22). A radially narrowing air outlet gap (21) is formed between the annular flow guiding protrusion (19) and the conical converging outer wall (20). The width of the radial air outlet gap (21) gradually decreases along the airflow direction to accelerate the airflow and form a high-speed thin-layer airflow; the annular guide protrusion (19) is used to guide the flow direction of the high-speed thin-layer airflow so that it is tangent to the surface of the spinning solution Taylor cone ejected from the liquid outlet needle (22) when it is ejected, thereby generating directional traction on the jet; the high-speed thin-layer airflow is rapidly dissipated in the whipping zone to avoid interfering with the stretching and refining process of the jet.

9. The high-speed electrospinning method based on an inorganic molecular chain solution according to claim 8, characterized in that, An elastic seal is provided at the connection between the fluid feed assembly (12) and the air outlet housing (15); The thickness of the gas regulating component (14) is 0.1~0.4mm, and the diameter of the regulating hole (18) is 0.3~0.9mm; The axial length of the annular guide protrusion (19) in the wall-mounted guide-directional pressurization structure (16) is 1.5 to 3.0 times the width of the radial air outlet gap (21), and the radial thickness of the annular guide protrusion (19) is 0.2 to 1 times the outer diameter of the liquid outlet needle. The conical converging outer wall (20) is configured as a converging structure along the axial direction of the nozzle, and its converging half angle relative to the nozzle axis is 3~20°, and the minimum radius of curvature of the conical converging outer wall (20) is 0.3~1.2 times the outer diameter of the liquid outlet needle. The radial width of the radial air outlet gap (21) is 0.1~1mm.

10. The high-speed electrospinning method based on an inorganic molecular chain solution according to claim 1, characterized in that, The high-speed pressure equalizing liquid supply spinneret (1) is connected to a high-voltage power supply (23). By adjusting the output voltage to -120~120kV, the airflow velocity to 0~100m / s, the injection speed of the spinning solution to 10~200mL / h, the receiving distance between the liquid outlet needle (22) and the spinning receiving device to 30~50cm, the spinning environment temperature to 25~35℃, and the environmental humidity to 20~90%, the spinning jet can achieve high-speed fiber formation and refinement. The prepared fibers have a diameter of 50~500nm and a single-nozzle spinning rate of 2~10kg / day.

Citation Information

Patent Citations

  • Supplementary electrostatic spinning ring nozzle of air current and electrostatic spinning device

    CN205223420U

  • Airflow-assisted coaxial spray head

    CN214637454U